Pannus microcystiformis Hindák (Cyanoprokaryota, Merismopediaceae) – a new species for Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Pannus microcystiformis Hindák (Cyanophyceae, Merismopediaceae) is recorded for the first time for Ukraine. The new finding is described and illustrated.
Keywords: cyanoprokaryotes, Pannus, the Crimea, Ukraine.